Participation of Women Farmers? in the Agricultural Research Process, Ethiopia - International Livestock Research Institute; International Potato Center; Wageningen University and Research (International Food Policy Research Institute, 2019)
Quantitative data collected to understand the level of women farmers? participation in four agricultural research processes ? design, testing, dissemination, and M&E. Data were collected in four woredas (districts), within the Ethiopian highlands (i.e. Basona Worena, Sinana, Lemo and Endamehoni), located in the regions of Amhara, Oromia, Southern Nations Nationalities People (SNNP) and Tigray respectively. Data were collected from women farmers who participate in the Africa RISING project and those who did not participate in the project.